Nonlinear Predictive Control Applied to Steam/Water Loop in Large Scale Ships. Issue 1 (2019) - Zhao, Shiquan; Cajo, Ricardo; Keyser, Robin De; Liu, Sheng; Ionescu, Clara M.
Abstract: In steam/water loop for large scale ships, there are mainly five sub-loops posing different dynamics in the complete process. When optimization is involved, it is necessary to select different prediction horizons for each loop. In this work, the effect of prediction horizon for Multiple-Input Multiple-Output (MIMO) system is studied. Firstly, Nonlinear Extended Prediction Self-Adaptive Controller (NEPSAC) is designed for the steam/water loop system. Secondly, different prediction horizons are simulated within the NEPSAC algorithm. Based on simulation results, we conclude that specific tuning of prediction horizons based on loop's dynamic outperforms the case when a trade-off is made and a single valued prediction horizon is used for all the loops.